Enhanced antibacterial activity of visible light activated sulfur-doped TiO2 nanoparticles against Vibrio cholerae. (15th August 2022) - Tariq, Fawad; Hussain, Rafaqat; Noreen, Zobia; Javed, Aneela; Shah, A.; Mahmood, Arshad; Sajjad, Muhammad; Bokhari, Habib; Rahman, Shams ur
Abstract: Pure and S-doped TiO2 nanoparticles were synthesized using a facile hydrothermal technique and the influence of sulfur doping on the structural and optical properties of TiO2 are highlighted. The focus of this work is to develop a photocatalyst having enhanced antibacterial activity against Gram negative bacteria. The crystallinity and phase composition of the synthesized nanoparticles were confirmed using X-ray diffraction (XRD) technique which showed that nanoparticles have anatase TiO2 structure which is in good agreement with the Raman studies. In addition, with S-doping crystallite size varied between 17.84 and 33.25 nm. The presence of S in the TiO2 matrix was confirmed by the elemental composition analysis carried out through EDAX measurements. FTIR spectra also revealed a band at 1068.01 cm −1, which is found to be associated with the Ti– O –S bond. UV-Vis measurements showed that the bandgap energy is, in general, decreased with the introduction of S in the TiO2 lattice. TiO2 doped with 40% S content (F-4) showed 71% bacterial growth reduction at concentration of 0.01 μg/mL. The safety of the synthesized nanoparticles was tested in vitro on hepatocellular carcinoma (Huh-7) human cell lines, which suggested that these particles are safe for the treatment of drinking water against Vibrio cholera.